Flexible polypyrrole/copper sulfide/bacterial cellulose nanofibrous composite membranes as supercapacitor electrodes. (10th February 2017) - Peng, Shuo; Fan, Lingling; Wei, Chengzhuo; Liu, Xiaohong; Zhang, Hongwei; Xu, Weilin; Xu, Jie
Highlights: PPy and CuS were successfully deposited on bacterial cellulose (BC) membranes. Electrochemical performances of composites as supercapacitor electrodes were investigated. The introduction of CuS remarkably improved the cycling stability of BC-based electrodes. Abstract: Polypyrrole (PPy) and copper sulfide (CuS) have been successfully deposited on bacterial cellulose (BC) membranes to prepare nanofibrous composite electrodes of PPy/CuS/BC for flexible supercapacitor applications. The introduction of CuS remarkably improves the specific capacitance and cycling stability of BC-based electrodes. The specific capacitance of the supercapacitors based on the PPy/CuS/BC electrodes can reach to about 580 F g −1 at a current density of 0.8 mA cm −2 and can retain about 73% of their initial value after 300 cycles, while the PPy/BC-based device could retain only 21.7% after 300 cycles. This work provides a promising approach to fabricate cost-effective and flexible nanofibrous composite membranes for high-performance supercapacitor electrodes.